Penetapan Kadar Flavonoid Total Pada Beberapa Bagian Tanaman Kepel (Stelecocharpus burahol Hook F. & Th) - Elfasyari, Trie Yuni (Jurnal Farmasi Udayana, 2020)
Kepel, Stelecocharpus burahol Hook F. & Th are originally grows in Indonesia. This plant is usually found in the Palace at Java island. Kepel has its own phylosophical meaning for the Palace, and the fruit is useful to maintain the beauty of princes of the Palace, the leaves are also nutritious to decrease cholesterol level. Efficacy of kepel is due to its contain active substance suchs us flavonoids, saponins, tannins, alkaloids, and steroids. There are currently no detailed data about levels of flavonoids in S. burahol. It is needs to be researched for determination of total flavonoid content ethanolic extract in different parts (young leaves, old leaves and seeds ) of S. burahol. Each part of plant were extracted by soxhlet using 96% ethanol as the solvent. Preliminary tests was conducted using cellulose plates as stationary phase and the mobile phase of n-butanol-acetic acid-aquadest (4:1:5, upper phase). Total flavonoid content was determined by visible spectrophotometric using alluminium chloride as chelating agent. The result of ANOVA analysis obtained showed that the total flavonoid content in ethanolic extracts leaves (young and old) and seeds, respectively (3.32±0.12); (4.82±0.08), and  (0.25±0.01)%. The 96% ethanol of old leaves extract of S. burahol showed the highest of total flavonoid content as 4.82±0.08%.